Leaks, whistleblowing and the public interest the law of unauthorised disclosures - Savage, Ashley (Cheltenham, United Kingdom Edward Elgar Publishing, 2016)
Ashley Savage provides an in-depth treatment of the law of unauthorised disclosures in the United Kingdom. Drawing upon extensive data obtained using freedom of information as a methodology and examples from comparative jurisdictions, he considers the position of civil servants, employees of the security and intelligence services and service personnel in the armed forces.
The consequences of making an unauthorised disclosure -- Protection as a journalistic source -- Legal protections for raising concerns -- Whistleblowing in the civil service -- Whistleblowing in the security and intelligence services -- Whistleblowing in the armed forces -- Final observations.
Includes bibliographical references (pages 272-278) and index.
Keywords: Leaks (Disclosure of information) -- Great Britain; Leaks (Disclosure of information) -- Cases -- Great Britain; Whistle blowing -- Law and legislation -- Great Britain; Whistle blowing -- Law and legislation -- Cases -- Great Britain; Leaks (Disclosure of information); Whistle blowing -- Law and legislation